A corpus-driven analysis of structural types of lexical bundles in court judgments in English and their translation into Lithuanian - Berūkštienė, Donata (Kalbotyra, 2017)
Formulaicity is one of the characteristic features of legal discourse, which manifests itself not only at the level of wording, “but also in the content, structure and layout” of legal texts (Ruusila & Londroos 2016, 123). Formulaic language, which includes phrasal and prepositional verbs, idioms, collocations, lexico-grammatical associations, lexical bundles, etc., are building blocks of legal discourse shaping legal text meanings. However, up to now, far too little attention has been paid to the nature of frequently occurring “sequences of three or more words that show a statistical tendency to co-occur” (Biber & Conrad 1999, 183), i.e. lexical bundles, in different genres of legal texts. Most studies in the field of lexical bundles in legal texts have only been based on one language (e.g. Jablonkai 2009; Goźdź-Roszkowski 2011; Breeze 2013), whereas translation-oriented contrastive studies on lexical bundles are lacking. In respect of the aforementioned gaps, the aim of this pilot study is to analyse structural types of lexical bundles in court judgments of the Court of Justice of the European Union in English and to examine the way these structures are rendered into Lithuanian. To gain insights into the frequency and structure of lexical bundles, the present study uses the methodological guidelines of corpus linguistics. The classification of lexical bundles into structural types is based on the framework suggested by Biber et al. (1999, 2004). For the purpose of this study, a parallel corpus of court judgments was compiled comprising approximately 1 million words of original court judgments in the English language and about 8 hundred thousand words of court judgments translated into Lithuanian. Lexical bundles in this research were identified using the corpus analysis toolkit AntConc 3.4.4 (Anthony 2015). A concordance program AntPConc 1.2.0 (Anthony 2017) was employed to find Lithuanian equivalents of the most frequent lexical bundles identified in the English court judgments. The evidence from this study suggests that different structural types of lexical bundles have more or less regular equivalents in Lithuanian; however, in most cases, these equivalents tend to be shorter.